KERAGAAN INDUSTRI KOPI DI KABUPATEN SAMBAS DAN KABUPATEN MEMPAWAH - Setyo Utomo, Rudy (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2015)
Abstract. Coffee is a product of West Kalimantan plantation which has been cultivated hereditary. In each district, coffee is traditionally processed into the coffee beans and ground coffee. This research issue is what products resulting from the processing of coffee cherries of the people and how the economic opportunities of processed coffee products that can be developed in West Kalimantan? The purpose of this study was to determine the type of coffee processing products which was processed by communities in Sambas and Pontianak regency District, and other types of commercially valuable products. This research was conducted in the district of Sambas and Pontianak regency. The study was conducted using financial analysis and multiple linear regression to determine the feasibility and the dominant factor Kalimantan coffee trade. Observation to know the types of people coffee processed products, availability of raw materials and technology. The results showed that the type of the people processed coffee products are coffee beans and ground coffee. Availability of raw materials coffee harvest small and decreasing every year. Coffee cultivation is not attractive to farmers as farm products, because it can not compete with farming of rubber, oil palm and other crops. Although the marketing of coffee available on the domestic market, nationally and abroad. The selling price of the coffee harvest is not in accordance with the cost of farming. There is a coffee product development opportunities in Sambas district, the wild civet coffee (Paradoxurus hermaphrodites).